2020
DOI: 10.1111/ssqu.12790
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Social Media Usage Status: Examination of Predictiveness of Digital Literacy, Academic Performance, and Fear of Missing Out Variables

Abstract: Objective. The aim of this study is to examine predictiveness of digital literacy, academic performance, and fear of missing out (FoMO) variables on social media usage (SMU) status. Methods. This relational study was conducted with participation of 1,284 students. For collection of the data a self-description form and also four other different data collection instruments were utilized. Data were analyzed through descriptive statistics and linear multiple hierarchical regressions analysis. Results. At the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Wolniewicz et al (2018) found that FoMO is strongly related to smartphone and social media use. In other words, FoMO plays an important role in the use of social media (Abel et al, 2016; Durak & Seferolu, 2020).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolniewicz et al (2018) found that FoMO is strongly related to smartphone and social media use. In other words, FoMO plays an important role in the use of social media (Abel et al, 2016; Durak & Seferolu, 2020).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…In other words, the higher the FoMO among college students, the higher their compulsive use of social media. As adolescents, college students experience FoMO because of emotional, social, and other factors (Durak & Seferolu, 2020). With the increase in the perceived FoMO among college students, their use of social media in class has also increased, resulting in the improvement of the degree of their social media multitasking.…”
Section: Indirect Effect Analysismentioning
confidence: 99%
“…The literature postulates that the possession of ICT resources necessary for the monitoring of educational programs is not a predictor of performance [47]. However, although a high percentage of students claimed to use ICT for learning mathematics, several authors have argued that their use is restricted by the low level of digital competence of most mathematics students [16,23], who use ICT mainly for Internet searches [40]. According to Eger's classification of digital competence [23], the majority of Melilla's mathematics students can be considered to be in the two lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although socioeconomic factors also influence the digital competences of teenagers, in general, young people have a basic competence level and their digital literacy is mainly focused on simple Internet searches and communications through chats and social media [40,41]. To this end, young people use mobile phones, usually with Wi-Fi, as their preferred communication and information device, as they are more practical and accessible [42,43].…”
Section: Ict Usesmentioning
confidence: 99%
“…Distintos estudios han observado que el FoMO se encuentra en la actualidad facilitado por el cómodo acceso a las redes sociales digitales a través de los dispositivos móviles (Wolniewicz et al, 2018;Yildiz Durak & Seferoğlu, 2020).…”
Section: Introductionunclassified